2015
DOI: 10.1111/pce.12525
|View full text |Cite
|
Sign up to set email alerts
|

Detoxification function of the Arabidopsis sulphotransferase AtSOT12 by sulphonation of xenobiotics

Abstract: Cytosolic sulphotransferases have been implicated in inactivation of endogenous steroid hormones and detoxification of xenobiotics in human and animals. Yet, the function of plant sulphotransferases in xenobiotic sulphonation and detoxification has not been reported. In this study, we show that the Arabidopsis sulphotransferase AtSOT12 could sulphonate the bacterial-produced toxin cycloheximide. Loss-of-function mutant sot12 exhibited hypersensitive phenotype to cycloheximide, and expression of AtSOT12 protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Our previous research indicated that AtSOT12 gene is a multiple stress inducible gene and can be highly induced by NaCl treatment ( Baek et al, 2010 ; Chen et al, 2015 ). The approximately 1 kb sequence in front of the initiation codon (ATG) of the AtSOT12 gene including 208 bp 5′-UTR, 207 bp promoter region, and 624 bp upstream sequence ( Figure 1A ) was validated to be a salt inducible promoter that could drive salt inducible expression of the luciferase reporter gene in Arabidopsis ( Jiang et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous research indicated that AtSOT12 gene is a multiple stress inducible gene and can be highly induced by NaCl treatment ( Baek et al, 2010 ; Chen et al, 2015 ). The approximately 1 kb sequence in front of the initiation codon (ATG) of the AtSOT12 gene including 208 bp 5′-UTR, 207 bp promoter region, and 624 bp upstream sequence ( Figure 1A ) was validated to be a salt inducible promoter that could drive salt inducible expression of the luciferase reporter gene in Arabidopsis ( Jiang et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that sulfate availability influences ABA under salt stress ( Cao et al, 2014 ). Perhaps AtSOT12 is one of the key enzymes regulating sulfur pools in the guard cells due to its strong induction by salt stress and its wide substrates selectivity ( Baek et al, 2010 ; Chen et al, 2015 ). Through modulating sulfur contents, AtSOT12 may regulate ABA levels thus play a role in guard cell function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We employed the proteins UGT74B1 and SOT16 from the Arabidopsis GLS pathway as bait and prey respectively. To evaluate specificity, we included the closely related SOT12, which functions in the synthesis of brassinosteroids 26 as well as detoxification of xenobiotics 27 . Co-transformation of FRB-NubG alone and the UGT74B1-containg bait construct did not give rise to activation of the reporter, demonstrating that this bait did not auto-activate the reporters under the applied conditions ( Fig.…”
Section: Resultsmentioning
confidence: 99%